Representasi nilai pendidikan islam multikultur dalam film ayat-ayat cinta 2 - Nanda Kartika Maharani; Solekhul Amin (Yayasan Azhar Amanaa Yogyakarta, 2026)
The value of Islamic education in a multicultural global society is crucial. This is because various countries around the world, including Indonesia, have numerous ethnicities, cultures, languages, and other ethnicities and religions (besides Islam) that coexist. Based on this background, the research questions in this thesis are: 1) What is the summary (synopsis) of the film